Mobile applications and English vocabulary among ninth graders at a public institution in Loja. School year 2022 – 2023 - Avila Abad, Andy Arley (2023)
Vocabulary knowledge is a fundamental part in the process of learning a new language, as it is involved in all four language skills. Nevertheless, based on previous studies and the researcher’s experience gathered through the practicums, it was noted that ninth-grade students still faced some difficulties with vocabulary proficiency. Consequently, this research aimed to increase English vocabulary through mobile applications among 41 ninth-grade students at a public institution in Loja during the 2022-2023 school year. The participants were selected using a convenience sampling method, and mobile applications such as Duolingo, Cram, and Hello English were employed as the tools for vocabulary improvement. For this purpose, this research followed the stages of the action research cycle proposed by Kemmis and McTaggart. Likewise, the mixed method was used to gather quantitative and qualitative data, which were collected through the pretest, posttest, questionnaire, peer observations, and reflective journals instruments. The data analysis was done using descriptive statistics for quantitative data, and thematic analysis for qualitative data. The results showed that after the intervention, ninth-grade students had a moderate increase of 2.94 points of mean difference between the pretest and posttest in the vocabulary aspects of Form (spelling, pronunciation); Meaning (associations); Use (grammatical functions, collocations). Likewise, it was concluded that ninth-grade students demonstrated positive perceptions about the use of mobile applications to increase their English vocabulary. This was because the mobile applications integrated engaging elements and interactive features, such as images, animations, leaderboards, flashcards, and quizzes that motivated students to engage in the vocabulary learning process. Keywords: Cram, duolingo, gamification, hello english, language learning, vocabulary aspects